Evaluation of plasticity of Kuantan clayey soil stabilized by rcycle and reuse material mixed with lime - Diana Erika, Phillip (2013)
The main purpose of this study is to determine the utilization of reuse and recycle materials such as fly ash, bottom ash, glass and OPEFB ash in order to improve the strength of the soil. Soils that contain high plasticity index especially clayey soils, is the most common problem that occurs during the construction of pavement and highway, retaining wall, foundation and other type of construction projects. Soft subgrade soil does not have the quality engineering properties which can support the structures efficiently. In order to overcome the problem, the soils have to be stabilized so that the engineering properties of the soil will improve. There are many method of soil stabilization that can be use, such as mechanical method and chemical method. However, soil stabilization by using mechanical method is very costly. Therefore, method of stabilization by adding chemicals additives into the soil is one of the alternative methods that can improve the engineering properties of the soil and it is more economical. This study is done to evaluate the plasticity of Kuantan Clayey soil stabilized by recycle and reuse material mixed with lime, in order to determine the most optimum content of stabilizers that can be used to reduce the plasticity index hence improve the properties of the soil.